Effect Of Product Quality, Brand Trust, and Brand Image on The Brand Loyalty of Aqua - Laily Faricha Nikmah; Rina Rosia (Sekolah Tinggi Ekonomi dan Perbankan Islam Mr. Sjafruddin Prawiranegara, 2023)
This study aims to analyze the effect of product quality, brand trust and brand image on the brand loyalty of AQUA. The population in this study is AQUA consumers in Central Java. Determination sample, using Cochrane formula, as many as 105 respondentsz. The data analysis method used is multiple linear regression. results study shows that product quality has a positive and significant effect on brand loyalty, then brand trust has a positive and significant effect on brand loyalty and brand image also has a positive and significant effect on brand loyalty. Meanwhile, product quality and brand trust simultaneously have a significant effect on brand loyalty, but brand image does not have a significant effect on brand loyalty for packaged drinking water products with the AQUA brand. Keywords: Product Quality, Brand Trust, Brand Image, Brand loyalty